Evaluation of Madaris Curriculum Integration for Primary Muslim Education in Mindanao: An Assessment of The Influence of Psychology - Kamarodin Abas Abdulkarim; Fitriah M. Suud (Universitas Muhammadiyah Yogyakarta, 2020)
This study evaluated the Madaris curriculum integration for Muslim primary education in Mindanao. It assessed the psychological effects of such integration on teachers and students in Arabic writing and reading, religiosity, Islamic values, and teacher professional development. This qualitative and quantitative research used a descriptive-evaluative design. The purposive sampling method was used to collect data using a questionnaire which was analyzed statistically. This study showed that the psychological effects of integrating teachers and students to Arabic writing and reading, religiosity, Islamic values, and teacher professional development worked well. Both teachers and students demonstrated the ability to write and read Arabic, values about God, Islam, people, the nation, and the environment.